Prediksi Sebaran Hama Tikus Pada Tanaman Padi Menggunakan Metode Backpropagation Neural Network - Arimawarni, Rafika; Sugiartawan, Putu; Murpratiwi, Santi Ika (INFOTEKS (Information Technology, Computer and Sciences), 2022)
OPT (Plant Pest Organisms) is any activity or activities that damage and kill plants, one of which is caused by pests, diseases, viruses, etc. In Bali, especially in Tabanan Regency, OPT cases are still very high. OPT in rice plants caused by rats is a problem faced by farmers and in the future, it must be prevented by knowing the spread of rats. Therefore, the purpose of this research is to help farmers prevent pest attacks so that rice productivity can be increased. In this study, the backpropagation neural network method was used to predict the distribution of rat pests on rice plants. This method uses previous data, namely from 2012-2021 when the data is processed and calculated until the smallest error value is obtained. In this study, data were obtained from calculating the distribution of pests in hectares which showed a percentage difference in accuracy error of 16.2%, which means that the prediction of this calculation is good enough to be used as a reference for further research